Regulating Palm Oil Zakat In Indonesia: Islamic Legal Politics, Normative Fragmentation, and the Quest for Legal Certainty - Zulkifli Nas; Anju Syahrin Marpaung (Yayasan Dar Arrisyah Indonesia, 2025)
Palm oil is one of Indonesia’s most strategic commodities, contributing significantly to national income and sustaining millions of rural livelihoods. Despite its substantial economic value, palm oil has not been systematically regulated as a zakatable asset, resulting in low compliance and limited contribution to national zakat collection. This article examines the regulation of palm oil zakat in Indonesia through the lens of Islamic legal politics by analyzing three normative domains: classical Islamic jurisprudence (fiqh), national zakat legislation, and regional fatwas issued by Islamic legal authorities. Employing normative legal research with statutory, conceptual, comparative fiqh, and Islamic legal politics approaches, this study reveals that palm oil zakat occupies an ambiguous legal position due to the absence of explicit regulation and the coexistence of competing juristic interpretations. While classical fiqh provides divergent doctrinal foundations, Indonesian zakat law adopts a generalized approach, and regional fatwas intensify legal pluralism by issuing conflicting rulings. This normative fragmentation undermines legal certainty, weakens zakat compliance among palm oil producers, and limits zakat’s redistributive potential. The article argues that palm oil zakat should be understood not merely as a doctrinal fiqh issue but as a product of Islamic legal politics requiring normative harmonization. It contributes to the literature by conceptualizing palm oil zakat as a case of regulated Islamic philanthropy shaped by legal and political authority and proposes policy-oriented recommendations for regulatory unification through coordinated roles of the state, zakat institutions, and Islamic scholars